2017
DOI: 10.1186/s12896-017-0389-7
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of an inactive xylose isomerase into a functional enzyme by co-expression of GroEL-GroES chaperonins in Saccharomyces cerevisiae

Abstract: BackgroundSecond-generation ethanol production is a clean bioenergy source with potential to mitigate fossil fuel emissions. The engineering of Saccharomyces cerevisiae for xylose utilization is an essential step towards the production of this biofuel. Though xylose isomerase (XI) is the key enzyme for xylose conversion, almost half of the XI genes are not functional when expressed in S. cerevisiae. To date, protein misfolding is the most plausible hypothesis to explain this phenomenon.ResultsThis study demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
0
17
0
1
Order By: Relevance
“…Numerous GroEL (60 kDa) and GroES (10 kDa) chaperonins were detected and assigned, amongst other taxa, to Clostridia and Bacteroidia ( Supplementary Table S3 ). Recently, the co-expression of GroEL-GroES was found to be imperative for the production of a functional xylose isomerase in Saccharomyces cerevisiae ( Temer et al, 2017 ). Xylose isomerases were detected in both bioreactor fractions and assigned exclusively to Clostridia and Bacteroidia ( Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous GroEL (60 kDa) and GroES (10 kDa) chaperonins were detected and assigned, amongst other taxa, to Clostridia and Bacteroidia ( Supplementary Table S3 ). Recently, the co-expression of GroEL-GroES was found to be imperative for the production of a functional xylose isomerase in Saccharomyces cerevisiae ( Temer et al, 2017 ). Xylose isomerases were detected in both bioreactor fractions and assigned exclusively to Clostridia and Bacteroidia ( Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Functional expression of a plant RuBisCO in E. coli was also recently shown to require co-expression of no fewer than five plant chaperones [ 74 ], highlighting the importance of expression of folding-assisting proteins in the formation of functional RubisCO complexes. In the case of GroEL and GroeS specifically, it was recently shown that their expression facilitates functional expression of several heterologous proteins in yeasts [ 28 , 75 , 76 ]. Further, their expression can potentially be beneficial in improving strain robustness against industrial fermentation conditions [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the codon-optimized XI of C. phytofermentans in S. cerevisiae resulted in a 46% increase in specific growth rate on xylose as compared to the strain expressing a non-optimized version of the gene [20]. XI from the bacterium Propionibacterium acidipropionici became functionally active in S. cerevisiae when coexpressed with GroEL-GroES chaperonin complex from E. coli [178]. More details on functional expression if XI in S. cerevisiae described in a recent reviews [72,103].…”
Section: Second-generation Ethanolmentioning
confidence: 99%